2004
DOI: 10.1590/s0074-02762004000700009
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the endogenous intestinal flora of swiss webster mice by experimental Angiostrongylus costaricensis infection

Abstract: The association between worm infections and bacterial diseases has only recently been emphasized. This study examined the effect of experimental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…infectious enteric diseases. For example, during infections with T. gondii a strong increase in Gram-negative bacteria leads to an aggravated intestinal Th1 immunopathology [21], but in experimental Angiostrongylus infection only insignificant increases in these bacteria could be detected [26]. Our studies showed no changes in Gram-positive bacteria but we could detect, albeit insignificantly, variations in Gram-negative bacteria from the fifth week of infection (Supporting information, Fig.…”
Section: Discussionmentioning
confidence: 57%
“…infectious enteric diseases. For example, during infections with T. gondii a strong increase in Gram-negative bacteria leads to an aggravated intestinal Th1 immunopathology [21], but in experimental Angiostrongylus infection only insignificant increases in these bacteria could be detected [26]. Our studies showed no changes in Gram-positive bacteria but we could detect, albeit insignificantly, variations in Gram-negative bacteria from the fifth week of infection (Supporting information, Fig.…”
Section: Discussionmentioning
confidence: 57%
“…For example, the impact of gut microflora on the host metabolism needs no additional ''justification'', nor the fact that parasitic infections directly affect the symbiotic mammalian-microbial equilibrium. 35 Abdominal pain, diarrhea, and blood in the stool are common symptoms of intestinal schistosomiasis. Under such circumstances changes in the concentration of ''mammalianmicrobial co-metabolites'', 36 usually reflected in alteration of urinary aromatic compounds such as hippurate or/and phenylacetylglutamine (PAG), are to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…costaricensis for ON, and this may be explained by factors other than genetic variation in rodent strains or humoral immune reactivity. For example, it has been shown that microbiota modifications associated with A. costaricensis infections may predispose a host to mucosal damage and septicaemia (Nobre et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%